Emerging and frontier markets : the new frontline for global trade - Goncalves, Marcus. (2014 digital library., 2015)
In today's fast-paced global economy, markets are sifting very swiftly, and the balance of trade and even political influence are following suit. It is important, therefore, that international business professionals, academics and students of global trade and international markets, and anyone interested on the latest developments taking place in global trade to be able to understand, compare and contrast the primary categories of emerging market business development, including its sub-categories, or maybe more appropriately, its sibling, the frontier markets.